2008
DOI: 10.1158/0008-5472.can-08-0316
|View full text |Cite
|
Sign up to set email alerts
|

Gain of Oncogenic Function of p53 Mutants Induces Invasive Phenotypes in Human Breast Cancer Cells by Silencing CCN5/WISP-2

Abstract: CCN5/WISP-2 is overexpressed in noninvasive breast cancer cells and tissue samples, whereas its expression is minimal or undetected in invasive conditions. CCN5/WISP-2 has been considered as an antiinvasive gene because CCN5/WISP-2 silencing augments the invasive phenotypes in vitro. However, the mechanism of silencing of CCN5 during the progression of the disease has been elusive. Because p53 mutations are associated with breast cancer progression and have been shown to correlate inversely with CCN5/WISP-2 ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 46 publications
6
57
0
Order By: Relevance
“…However, their effect in terms of offering new concepts of the molecular network of human breast cancer development, diagnostics, or therapeutic modalities remains limited. Over the last several years, after the identification of CCN5 in noninvasive human breast tumor cells and samples by using RNA differential display analysis (14), CCN5 has been implicated as having an important role in human breast disease and other cancers as well (9,10,14,20,(29)(30)(31)(32)(33). The present immunohistochemical and in situ hybridization analysis studies have shown a differential expression profile of CCN5 in human breast samples.…”
Section: Discussionmentioning
confidence: 57%
“…However, their effect in terms of offering new concepts of the molecular network of human breast cancer development, diagnostics, or therapeutic modalities remains limited. Over the last several years, after the identification of CCN5 in noninvasive human breast tumor cells and samples by using RNA differential display analysis (14), CCN5 has been implicated as having an important role in human breast disease and other cancers as well (9,10,14,20,(29)(30)(31)(32)(33). The present immunohistochemical and in situ hybridization analysis studies have shown a differential expression profile of CCN5 in human breast samples.…”
Section: Discussionmentioning
confidence: 57%
“…[19][20][21] Briefly, 50 ÎŒg total protein was separated by SDS-PAGE and transferred to nitrocellulose membrane (Trans-blot transfer medium, Bio-Rad). The membranes were probed with primary antibodies for a specified period of time as per the manufacturer's instructions.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…For example, silencing of CCN5 in MCF-7 non-invasive carcinoma cells by CCN5-specific shRNA significantly enhances motility and EMT, and it modulates the expression of some genes associated with invasive phenotypes of cancer cells Dhar et al 2008;Fritah et al 2008). In CCN5 knockout ER-α positive breast cancer cells, IGF-1 and EGF lost their mitogenic effect Dhar et al 2007b), but possibly gained aggressive phenotypes (i.e., Fig.…”
mentioning
confidence: 99%